Modelling the Influence of Aquatic Vegetation on the Hydrodynamics of an Alternative Bank Protection Measure in a Navigable Waterway. (28th June 2016) - Weber, A.; Zhang, J.; Nardin, A.; Sukhodolov, A.; Wolter, C.
Abstract: Computational fluid dynamics (CFD) has become an effective tool for assessing hydrodynamics in complex environments. This paper reports on a CFD study of navigation‐induced flows in a shallow, wave‐protected, littoral habitat of the urban Spree River. It was constructed as a rehabilitation structure for aquatic organisms and subject to abundant growth of aquatic and riparian vegetation. This study aims to quantify the hydrodynamics induced by vessel movements and its consequences for water exchange and lateral connectivity between the habitat and the main channel with three representative, natural densities of aquatic plants. The simulations revealed both high efficiency of the rehabilitation structure in reducing hydrodynamic forces in the littoral and a superimposed reduction of hydrodynamic forces, and increase of flushing time with increased plant cover. Higher vegetation density resulted in lower wave propagation and lower connectivity of the rehabilitation structure with the fairway. Thus, natural succession of aquatic vegetation in the shallow habitats leads to increasing isolation and finally to terrestrialization. Maintaining the functionality of the rehabilitation structure as habitat for other aquatic organisms requires either plant removal or preferably adaptive modification, e.g. by successively increasing the openings to the main channel and letting the plants take over the protective function of the technical facilities. The developed CFD model helps to find hydrodynamically optimized solutions and to support decision‐making process for maintaining littoral refuges for plants and weak swimming organisms in navigable waterways. Copyright © 2016 John Wiley & Sons, Ltd.